High intensity exercise warm-up, inhibition of glycolysis and its practical consequences - Hofmann, P.; Müller, A.; Tschakert, G.; Moser, O.; Gröschl, W. (Abstractband der 6. Internationalen Konferenz Wissenschaft und Skisport. 14.-19. Dezember 2013, St. Christoph am Arlberg, Österreich, 2013)
Warm-up is a substantial part of every high intensity sport. The impact of high intensity warm-up close to the competition workout on energy metabolism has not been investigated in detail yet. It is suggested that elevated lactate (La) levels influence the rate of glycolysis in a subsequent anaerobic work bout such as performed in alpine skiing.